Liability of a Notary for Factual Errors in Authentic Deeds: Tanggung Jawab Notaris atas Cacat Faktual dalam Akta Autentik - Yapferonica, Yapferonica; Djaja, Benny (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Authentic deeds function as legal instruments with perfect evidentiary value and play a central role in ensuring legal certainty within the national legal system. Specific Background: Notaries, as public officials authorized to formalize legal acts, are required to uphold prudence, professionalism, and compliance with statutory regulations in drafting authentic deeds. Knowledge Gap: Despite normative limitations that place notarial responsibility primarily on formal aspects of deeds, ambiguity persists regarding the extent of liability when factual defects arise from negligence or intentional misconduct. Aims: This study aims to examine the legal considerations in determining notarial liability for the substance of authentic deeds and to analyze the forms and scope of legal responsibility related to deeds that do not reflect factual circumstances. Results: Using a normative juridical approach with statutory and conceptual analysis, the study finds that notarial liability may extend beyond formal responsibility when there is insufficient verification, lack of prudence, or active involvement in inserting inaccurate information into authentic deeds. Such conditions may result in administrative, civil, and criminal consequences, particularly in cases involving falsification, fraud, or misuse of authority. Novelty: This study emphasizes multidimensional notarial liability by distinguishing formal and material accountability while integrating prudential principles, professional ethics, and criminal law perspectives. Implications: The findings underline the necessity of rigorous document verification, ethical compliance, and professional integrity to preserve the credibility of authentic deeds as instruments of legal certainty and public trust. Highlights: Verification duties determine accountability boundaries in drafting official legal documents. Negligence and intentional misconduct may trigger administrative, civil, and criminal sanctions. Professional ethics and prudential standards remain essential for maintaining evidentiary credibility. Keywords: Notary, Accountability, Authentic Deeds